PARTISIPASI PENDIDIKAN DAN TENAGA KEPENDIDIKAN TERHADAP PROGRAM ADIWIYATA - Qurrotaini, Lativa; Bahij, Azmi Al (Jurnal Holistika, 2017)
This research was promoted throught the adiwiyata school program which is given  by monistry of environment and forestry, indonesia.the purpose of  this study was to determine the levels of participation among teachers and edicators at elementary school darma karya ut and state elementary school tanah tinggi 3 banten, related to their success in adiwiyata green school program. The tome ogf the study was started from desember 2015 to may 2016. While thepopulation selected on the study was all teacher and educators from both thopse elemantary schools, by using disproportionate stratifield random sampling technique. The sresult in this study found that there awa a high participation among teacher and aducators, in promoting knowledge and awarness about environmental conservation effort among the student community . thus, the schools’ succes was not apart from their high participation toward the frindly and caring school environment